Influence of pulse electrical discharges on the microstructure of the electrode system drill - Shuyushbayeva, N.; Altayeva, G.; Stoev, M.; Akhmadiev, B.3. (Publishing House of the KarSU named after E.A.Buketov, 2016)
The paper is considered practicalities of the electro-hydraulic drilling. The basis of this method is a unique phenomenon - a method of directly transforms of electrical energy into mechanical energy of the shock waves that accompany electrical discharges in conditions a limited spatial volume of water in the bottom of the well. The power a shock wave is allows to effectively disruption is not only the solid rocks but also influences the condition of the drilling system. Study the structure and quality of the surface of the electrode system of the drill, and the character of the changes after the electrohydropulse of processing. Conducted spectral analysis of the microstructure of the melted portions of the surface drill electrodes resulting from the impact of underwater spark discharge. Experimentally are installed regularities of erosive of wear the metal electrode from the energy parameters and the number of electro-impulses.
Keywords: electrode; electrohydraulic pulse; energy; discharge